ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PENYALURAN KREDIT USAHA MIKRO DAN KECIL (UMK) (Studi Kasus pada PT BPR Modern Expres di Kota Ambon) - Joseph. R. Patiruhu (Soso-Q : Jurnal Manajemen, 2017)
The study aims to analyze influence of Capital Adequacy Ratio (CAR), Third Party Fund (DPK), and Operating Expenses to Operational Income (BOPO) to Loan to Deposit Ratio (LDR) as a Credit Distribution Proxy. Population  in this study is Government  Bank Maluku and North Maluku with 20 samples(quarterly) for 5 year  period 2011-2015.The method used in this research is descriptive analysis anf multiple regression analysisThese result indicates that the independent variables  CAR, insignificant  influence; LDR and BOPO  are positive and significances influences to LDR. Based to R2 test showed that the  ability to explain the independent  variable on the dependent variable LDR amounted to 51,9 % while remaining 48.1 % is influences by other variables outside the independent variable used in this study Keyword: CAR, DPK, BOPO => LDR